Pre-charge pressure effects on isothermal and adiabatic energy storage capacity for dual hybrid hydro-pneumatic passenger car driveline - R. A., Bakar; L. M., Gan; M. M., Tahir; A. A., Yusof (Centre for Advanced Research on Energy (CARe), 2017)
The hydro-pneumatic accuurnulator is broadly applied in heavy industry' and the automotive sector as a leaking compensator, dampening and energy storage. The performance of charcing has a correlation to the thermal process condition because it involves the compression of nitrogen gas. The research was conducted to study the role of thermall process condition and its impact. The simulation study has. been carried out by using, Automation Studio software. The result has shown that the isothermal storage is more effieient than adiabatic in term of effective volume. However, adiabatic is faster with regards to filling time compared to isothermal.